PENGARUH TERAPI AKUPRESUR DAN PIJAT OKSITOSIN TERHADAP PENINGKATAN PRODUKSI ASI PADA IBU POSTPARTUM DI RSUD JOMBANG - Khabibah, Lailatul; Mukhoirotin, Mukhoirotin (Universitas Pesantren Tinggi Darul Ulum, 2019)
ABSTRACTLittle milk production in the first days of childbirth is an obstacle in breastfeeding. Efforts can be made to increase breast milk production with acupressure therapy and oxytocin massage. The purpose of this study is to prove the comparison between acupressure therapy and oxytocin massage in increasing breast milk production in postpartum mothers. The study design used quasy experiments with the Pre-Post Test Control Group Design approach. The study sample was 24 postpartum mothers who were divided into 3 groups. The sampling technique uses purposive sampling Measurement of breast milk production was measured using a Weighing Test. Data were analyzed by one way anova test and paired t-test with ? ?0.05. The result of this study showed that there was an effect of acupressure therapy and oxytocin massage on Breast Milk production in postpartum mothers p<0.05 and there was no different in effect of acupressure therapy and oxytocin massage on Breast Milk production in postpartum mother?s p>0.05. Acupressure therapy and oxytocin massage can increase the expenditure of milk production in postpartum mothers, because both of these actions stimulate the hypothalamus and continue to the anterior pituitary to release the hormone prolactin and posterior pituitary to release the hormone oxytocin, there by increasing the production and expenditure of milk.Keywords: oxytocin massage, breast milk production, post partum, acupressure therapi